An analysis of supply response of rapeseed-mustard in different regions of Uttar Pradesh - Arpita Gangwar; Virendra Singh (Journal of Oilseed Brassica, 2026)
The continuing imbalance between increasing demand and slow growth in supply of oilseeds is a majorconcern which needs to be addressed seriously. The increase in the production of oilseed has to comethrough increase in acreage and /or productivity of the oilseeds. Uttar Pradesh is a very important state in thecountry from agricultural point of view, which occupying second position in rapeseed-mustard production. InUttar Pradesh, an attempt was made to examine the economic factors on supply response of rapeseed mustardin different regions, and at aggregate level. The present study evaluated the impact of price andselected non-price factors on the area of rapeseed-mustard, and to analyse the short and long-run priceelasticities. This macro framework study used 20 years (1989–90 to 2008–09) secondary data regardingarea, productivity, farm harvest price of crops, farm harvest price of competing crops, monsoon seasonrainfall, percentage irrigated area of crops, and competing crop (gram). The double log Nerlovian laggedadjustment model used in present study postulates that the actual acreage under a crop in each period isadjusted in a proportion to the difference between the desired acreage in the long run equilibrium, and theactual acreage under it in the preceding year. The short-run price elasticities of acreage are directly obtainedfrom logarithmic form of the model function. As the value of coefficient of adjustment usually lies betweenzero and one, the value of ‘B’ close to the unity indicates that the adjustment process is very fast. When thevalue of ‘B’ is close to zero, the implication is that the adjustment process is very slow to the changing pricesand other non-prices factors. If the value of ‘B’ is greater than one it would mean that the farmers over adjustto the planned acreage. Speed of adjustment implies the number of years required to realize 95 per cent of theprice effect which was estimated using the formula suggested by Krishna, (1992). The results showed thatacreage response of rapeseed-mustard to the price of rapeseed-mustard was positive and significant in allregions of Uttar Pradesh, except Bundelkhand region. The response to the price of competing crop (gram),however, was positive and significant only in case of Central region. The lagged yield of rapeseed-mustardwas found to be positive and significant only in Bundelkhand region. Rainfall had strong impact on acreageunder rapeseed-mustard both at aggregate and regional levels. The percentage irrigated area showedpositive and significant impact in all regions, except the Central region. The percentage irrigated area ofcompeting crop gram was positive and significant only in the Central region, but it was negative andsignificant at state level. Lagged area under the concerned crop was positive and significant for Western,Central, and state as a whole. In all the cases, price as well as yield risk did not play any significant role inacreage allocation of rapeseed-mustard, except in the Central and Bundelkhand regions where the yield riskwas positive and significant. The short run price elasticities varied from region to region. The impact of priceswas the highest in the Western and lowest in the Central region. The comparative closeness of long runelasticity to the short run elasticity in central region revealed a greater degree of adjustment in this region.The results of speed of adjustment showed that the farmers of Central and Bundelkhand regions would takeless number of years to realize 95% of price effect as compared to the farmers of other regions.